ANALISIS KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN SEMARANG - Bhaskoro Adhi Nugroho, 09.05.52.0040; Maryono, Maryono (Students Journal of Accounting and Banking, 2014)
Local taxes and levies constitutes acceptance pemrintah Original area of sector revenue (PAD). The amount of local tax revenue and levies greatly influenced by many types of taxes and levies are applied and based on valid peraturanyang related to local taxes and levies such. Researchers analyzed the contribution of local taxes and levies to local revenues Semarang districtÂ from 2008 to 2012.Contribution of local tax revenue and levies based ond data taken at the Revenue Office of Management and Asset Finance Regions (DPPKAD) in the period from 2008 to 2009 give an average contribution of local taxes by 22.12% per year and the average contribution levies by 58 , 59% per year. In order to improve the ability of local governments to implement regional autonomy, the central government set the Law No. 28 Year 2009 on local taxes and levies. The results in the year 2010 - 2012 PAD acceptance in Semarang district increased 20.44% per year, the average contribution of local taxes rose to 32.20% per annum.In order to increase the revenue receipts and increase government revenue district ofÂ Semarang need dilakukanya voting-ballot types of local taxes and levies are based in accordance with Law No. 28 of 2009 to establish the area as a basis for regulation through the collection of rules.Keywords: local taxes, levies and revenue.